Predictors of traumatic birth experience among a group of Iranian primipara women: a cross sectional study - Solmaz Ghanbari-Homayi; Zahra Fardiazar; Shahla Meedya; Sakineh Mohammad-Al; Mohammad Asghari-Jafarabadi; Eesa Mohammadi; Mojgan Mirghafourvand (BMC, 2019)
Abstract Background Traumatic birth experience has undesirable effects on the life of the mother, child, family, and society. The identification of predictive factors can be useful in improving birth experiences among women. This study aimed to assess the prevalence of a traumatic birth experience and identify its predictors among a group primiparous women. Methods A cross-sectional study was conducted among 64 health centres in Tabriz, the second largest city in Iran. Cluster sampling was used to recruit 800 eligible women at one to 4 months postpartum. The Persian version of the Childbirth Experience Questionnaire was used to measure the womens' birth experiences. Data were collected through face to face interviews and analysed mainly by multivariable logistic regression. Results The prevalence of traumatic birth experience was 37% in the study group. The independent predictors of the traumatic birth experience were related to antenatal and intrapartum factors. The antenatal predictor was the lack of exercise during pregnancy (OR = 2.81, CI 1.40-5.63, P = .003) and the intrapartum predictors were the absence of pain relief during labour and birth (OR = 4.24, CI 2.12-8.50, P < .001), and the fear of childbirth (OR = 3.47, CI 1.68-7.19, P < .001). Conclusions The findings revealed the high rate of traumatic birth experience among the primimarous women and identified the importance of a woman-centered care where a woman can actively make decision about the care she receives receive during labour and birth.